PENGARUH JUMLAH HELAI BENANG TERHADAP NILAI ESTETIKA DAN MUTU SULAMAN TERAWANG HARDANGER PADA SARUNG BANTAL SOFA - Yuliarma; Refi Norita (Jurnal Dimensi Seni Rupa dan Desain, 2023)
Hardanger embroidery is embroidery done on plain weave fabrics. The results of the embroidery are in the form of geometric holes. The background of this research is that hardanger embroidery appears with aesthetics an poor quality. The aim of the research was to improvw the aesthetics and quality of hardanger embroidery including a.) to determine the effect of using 1 thread on the aesthetic value and quality of hardanger embroidery b.) to determinne th effek of use 2 thread on the aesthetic value and quality of hardanger embroidery c.) to determine the effek of use 3 thread on th aesthetic value and quality of hardanger embroidery. This research was experimental research. The statistical test result with SPSS obtained significant aesthetic value of hardanger embroidery was 0.97, 0.60 and 0.61 with p<0.05 so that H0 is accepted. There is no significant effect on the aesthetics of embroidery using a different number of threads. The significant value of embroidery quality is 0.000 with p>0.05 so H0 is rejected. There is a significant effect on the quality of embroidery using a different number of thread strans. Keywords: Terawang; Aesthetic, Quality